Business Plan Strategy For Developing The Carp Farming Business In The Kasomalang Area, Subang, West Java - Antoni, Faisal; Suganda, Uce Karna (UNIVED Press, 2026)
This study aims to analyze the development strategy of carp (Cyprinus carpio) farming using a fast-flowing pond system in Subang Regency. The background of this study is based on the high potential for carp production, which is still constrained by limited capital, mastery of farming technology, and suboptimal market access. The main issues include sustainable farming techniques, factors affecting success, marketing strategies, and government support for farming businesses.The research method used was qualitative with a case study approach at CV. Faston Sejahtera. Data were obtained through observation, interviews, and literature studies, then analyzed using the SWOT approach and business feasibility. This analysis aims to assess the strengths, weaknesses, opportunities, and threats faced by the company in developing its business. The results of the study indicate that carp farming is feasible and has prospects for sustainable profits. SWOT analysis places the business in an aggressive (growth-oriented) strategy with strengths in strategic location, availability of superior seeds, and high market demand. External opportunities are supported by fish consumption trends and government policies. However, this business still faces weaknesses in the form of limited capital and technology as well as threats from price fluctuations, competition, and the risk of fish disease.In conclusion, the development of carp farming in Subang has great potential if accompanied by strengthened business management, expanded access to capital, technological innovation, and more effective marketing strategies.